Stavrakakis, Y. and Katsambekis, G. (2024). Research Handbook on Populism. Edward Elgar Hardback ISBN: 9781800379688. ebook ISBN: 9781800379695 - Newth, George (The Greek Review of Social Research, 2024)
N/A